Modification of a Previously Described Arteriovenous Malformation Model in the Swine: Endovascular and Combined Surgical/Endovascular Construction and Hemodynamics - Siekmann, Ralf; Wakhloo, Ajay K.; Lieber, Baruch B.; Gounis, Matthew J.; Divani, Afshin A.; Hopkins, L. Nelson (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: The rete mirabile in swine has been proposed as an arteriovenous malformation (AVM) model for acute experimental studies through surgical creation of a large carotid-jugular fistula. This report describes two endovascular modifications to simplify the surgical creation and provides hemodynamic parameters for the AVM model.METHODS: An AVM model was created in 29 animals to study n-butyl 2-cyanoacrylate polymerization kinetics. The common carotid artery (CCA) was punctured and a guiding catheter was inserted tightly into the origin of the ascending pharyngeal artery (APA). The CCA was ligated proximal to the catheter to create a pressure drop across the rete, which represented the AVM nidus. The catheter hub was opened whenever needed and served as the venous drainage of the AVM nidus. The contralateral APA served as the arterial feeder. Instead of the surgical ligation of the CCA, a temporary balloon occlusion was performed in three animals.RESULTS: A mean pressure gradient of 14.9 ± 10.5 mm Hg (range, 4–42 mm Hg) was measured across the rete. The mean flow rate was 30.4 ± 14.2 mL/min (range, 3.5–46 mL/min), as measured at the venous drainage.CONCLUSION: The endovascular and combined surgical-endovascular rete AVM model in swine is easy to construct and is less time-consuming than are the currently used models for acute experimental studies. Hemodynamic parameters can be monitored during the entire experiment and correspond to values found in human cerebral AVMs.